Young patient with hantavirus-induced myocarditis detected by comprehensive cardiac magnetic resonance assessment - Krumm, Patrick (BMC Infect Dis, 2019)
BACKGROUND: We report a case of hantavirus-induced myocarditis in a young adult. Hantavirus showed a rapid increase of infections in the year 2017. Only scarce data is available about potential myocardial involvement in hantavirus infections. With ECG and echocardiography providing often inconclusive results, a multiparametric cardiac magnetic resonance protocol with distinct myocardial tissue characterization seems to be the adequate tool for detecting even slight myocardial alterations. CASE PRESENTATION: This case started with the presentation of young adult suffering from headache and abdominal pain. Thrombocytes were decreased, creatinine was elevated, and there was massive proteinuria. Puumala virus IgG ELISA turned out to be positive, and specific antibodies (IgG and IgM) could be detected in the serum, and confirmed by immunoassay. The patient was admitted to the nephrology department for supportive therapy. Few days later, the patient reported chest pain and dyspnea. High sensitivity troponin I rose up to 0.32 μg/l (normal range below 0.04 μg/l) with an increase of the creatinkinase to 319 U/l (normal max. 190 U/l), no dynamic ECG changes could be observed. Echocardiography revealed a normal left ventricular function without regional wall motion abnormalities, no pericardial effusion or valve abnormalities, coronary artery disease could be excluded by computed tomography. A multiparametric cardiac magnetic resonance protocol including recent mapping techniques confirmed myocardial involvement induced by acute hantavirus infection. In the next few weeks, the patient’s state of health rapidly improved and symptoms of chest pain and dyspnea disappeared. Follow up multiparametric CMR exam showed substantial decrease of the previously observed myocardial alterations during acute hantavirus infection suggesting myocardial healing. CONCLUSIONS: This case demonstrates that a CMR protocol including recent mapping techniques and established late gadolinium enhancement technique is an adequate non-invasive tool for both 1) initial detection, and 2) follow up of patients with hantavirus-induced myocarditis, which might be more common than previously known. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-018-3658-8) contains supplementary material, which is available to authorized users.